Legal protection of employee health when working with nanoparticles. Comments on the appropriateness of introducing european legal regulations - Maciej Jarota (Nofer Institute of Occupational Medicine, 2019)
The aim of this publication is to analyze legal regulations related to occupational health and safety in the context of the development of nanomaterials technology. The author reflects on the possibility of introducing legal structures at the European Union level to facilitate protecting employee health in the work environment related to nanoparticles. Employers, in the scope of their duties, should take the necessary measures to ensure the safety and health of employees, including the prevention of threats related to the performance of official duties, information and training, as well as providing the necessary organizational framework and resources. Different organizations or research institutes are working on researching the numerical occupational exposure limits for nanoparticles, but the right direction to protect workers' health from exposure to nanoparticles is still at an early stage of diagnosis. It seems important to study the extent to which current methods and tools for risk assessment are up to date, and the elements that should be adapted to the characteristics of nanoparticles. The paper attempts to answer the question of whether the current legal protection of employees, in the context of risks and threats posed by nanotechnology, is sufficient. Med Pr. 2019;70(5):633-47